Handbook of diabetes - Bilous, Rudy W.; Donnelly, Richard, 1960-; Idris, Iskandar (Wiley-Blackwell, 2021)
"For over 20 years, our Handbook of Diabetes has been the perfect practical companion to its parent Textbook of Diabetes, one of Wiley's key medical copyrights and widely considered the most clinically-focused diabetes reference book. Cheaper, more practical/accessible, and less scientifically dense than reference books, the Handbook of Diabetes is perfect reading for all health professionals with an interest in diabetes, especially doctors in speciality diabetes/endocrinology training, foundation level doctors, diabetes specialist nurses, and GPs. Its focus is clearly on the clinical aspects of the disease and in particular, how to best manage patients suffering from diabetes. As well is the strong emphasis on the clinical, readers love its visual look and high production standards. Clear and easy-to-navigate, it's packed full of case histories, key learning/practice points, landmark clinical trials and additional resources to consult in every chapter, and benefits from a well-designed and full colour interior throughout. To support the text, over 400 figures, including 300 beautifully drawn colour diagrams provide the reader with a visual element unmatched in other diabetes handbooks"- Resumé vydavatel